Severity of hepatitis & it's correlation with dengue hemorrhagic fever: Experience from a tertiary care hospital - Islam, Ariful; Bashar, Jinan; Rahim, Muhmmad Abdur; Uddin, Khwaja Nazim (Bangladesh Critical Care Journal, 2020)
Background: Dengue fever and dengue hemorrhagic fever is one of the most frequent febrile viral infections in our community as well as among patients admitted in Internal Medicine Department. This study examined the extent of hepatic involvement in dengue hemorrhagic fever Objectives: To evaluate the incidence of hepatic involvement and its correlation in dengue syndromes. Design: This Cross-sectional observational study done in Internal Medicine Department of BIRDEM General Hospital. Method: A total 50 patients were included in this study who was serologically positive dengue fever patients (IgM ± IgG). These patients were admitted to Internal Medicine Department of BIRDEM General Hospital from July, 2011 to December 2011. Hepatic transaminases (AST and ALT) of these patients were measured and correlation was seen by standard methods. Informed written consent was taken from patients. Results: Total number of patients was 50; their mean age was 45.98±18.37 years. Male: Female ratio was 1:1.85. Common co-morbidities were DM (48%) and hypertension (26%), CKD (8%) and bronchial asthma (6%). Among the 50 patients 23 had CD (Classical Dengue), 20 had DHF (Dengue Hemorrhagic Fever) grade 1, six had DHF grade 2 and one had DHF grade 3. Mean AST among CD and Grade 1, 2, 3 DHF were 58.48±8.99, 96.65±9.06, 217±31.82, 296.00 respectively. Mean ALT among CD and grade 1, 2, 3 DHF were 52.39±9.08, 88.10±13.14, 181.67±12.11 respectively. There was significant difference between AST (P value ˂0.001) and ALT (P value ˂0.001) in each group of patients. It was observed that rise of AST and ALT was significantly higher in grade 1, 2 and 3 when compared with CD. AST and ALT was higher in grade 2 then grade 1 DHF patients. Conclusion: Rise of hepatic transaminases is common in patients with dengue syndromes. There is significant rise in AST then ALT. The rising pattern of these enzymes correlates with severity of dengue syndromes Bangladesh Crit Care J September 2020; 8(2): 76-80